Towards the elimination of mother to child transmission of syphilis 2015-2020: practice and progress in Zhejiang province, eastern China - Hong Wang; Xia Ying; Dan Lin; Muhuza Marie Parfaite Uwimana; Xiaohui Zhang (BMC, 2023)
Abstract Objectives To estimate the progress towards elimination of mother-to-child transmission (EMTCT) of syphilis in Zhejiang province. Methods Data were obtained from Zhejiang provincial EMTCT network. Childbearing women infected with syphilis during 2015-2020 were recruited. Joinpoint mode was used to analyze changing trends in syphilis screening, treatment and adverse pregnancy outcomes (APOs). Changing trends were presented as the annual percentage of change (APC). Multivariate logistic regression mode was used to analyzerisk factors of APOs. Results Of 3,658,266 participants, an average maternal syphilis incidence was 0.38%. From 2015 to 2020, the coverage of syphilis screening in pregnancy (96.31% to 99.24%; P < 0.001) and coverage of antenatal health care (ANC) within 13 gestational weeks (55.27% to 77.82%; P = 0.002) were increased.The coverage of maternal syphilis treatment(88.30% to 98.25%; P = 0.001) and adequate treatment (66.92% to 83.37%; P = 0.001) were also increased. Over the years, the APC was -19.30% (95%CI:-24.33 ~ -13.92, P = 0.001) in perinatal death,-26.55% in congenital syphilis(95%CI:-38.75 ~ -11.92, P = 0.009), and -14.67% in other neonatal complications (95%CI:-23.96 ~ -4.24, P = 0.019).In 2020, 11.58% of women had APOs. The rate of syphilis infection during pregnancy increased among women aged (< 20 years) or (≥ 35 years), multiparous, and with pregnancy complications (all P < 0.05).APOs risk increased in women with higher maternal RPR/TRUST titers while it decreased in women who had (adequate) therapy, early ANC, and aged in 21-34 years (all P < 0.001). Conclusions Despite steady progress towards the goal of EMTCT in implementing universal screening and treatment, syphilis continuously affects a large number of pregnant women. Increasing vulnerable women, small proportions of inadequately treated and delay in early ANC should be noticed.